A retrospective analytical study on causes and contributary factors of maternal mortality - Jariwala, Sherebanu Zainulabedin; Jain, Mahima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Maternal mortality has long been considered as a very good indicator for healthcare quality provided. Pregnancy is considered to be a physiological phase in the lifetime of a woman carrying serious implications on morbidity and mortality. It has been agreed upon that many of the maternal deaths in developing countries can be prevented. This study aimed to study the prevalence of maternal mortality during April 2022- March 2023 in Civil hospital Ahmedabad, tertiary care centre. Methods: It’s a retrospective observational study done at a tertiary care centre in Ahmedabad, Gujarat India. Maternal deaths from April 2022 to March 2023 were looked into. Maternal mortality ratio and causes for the maternal deaths were analyzed and compared. Demographic details were collected and data regarding parity, mode of delivery, gestational age at delivery, antenatal checkups, co morbid conditions, causes of death were noted and neonatal outcomes were noted. Results: Overall live birth between April 2022-April 2023 were 7700 out of which number of LSCS were 2569 and remaining were vaginal deliveries, the number of maternal deaths were 39 (MMR-505.8/100000 live births). Most common direct c causes were severe preeclampsia/eclampsia and their complications 14 cases (35.89%), followed by sepsis 6 cases (15.38%) and PAS leading to PPH 5 cases (12.82%). The most common indirect cause was sickle cell anemia. Conclusions: Preeclampsia and their complications and sepsis emerged as the greatest killers. Many of the reasons of maternal mortality were found to be preventable. Early identification and stratification of risks with prompt initiation of necessary management measures are necessary to prevent these deaths.